MODEL PENINGKATAN KINERJA KARYAWAN HOTEL - Sutrisna, Arga; Putri Lestari, Suci; Arisman, Ari (LP2M Universitas Perjuangan Tasikmalaya, 2025)
This study aims to identify factors that shape employee performance in the Indonesian hotel industry, specifically by analyzing the influence of competence, emotional intelligence, work-life balance, and motivation on employee performance, both collectively and individually. The method used is a survey with data collection through questionnaires distributed to respondents, namely hotel employees in Indonesia, with a focus on Pangandaran Regency. The results of the study revealed that competence, emotional intelligence, work-life balance, and motivation have a significant effect on employee performance, both simultaneously and partially.